Effects of Perinatal Fluoride Exposure on Short- and Long-Term Memory, Brain Antioxidant Status, and Glutamate Metabolism of Young Rat Pups - Bartos, Mariana (2019)
Exposure to fluoride (F) during the development affects central nervous system of the offspring rats which results in theimpairment of cognitive functions. However, the exact mechanisms of F neurotoxicity are not clearly defined. To investigate theeffects of perinatal F exposure on memory ability of young rat offspring, dams were exposed to 5 and 10 mg/L F during gestationand lactation. Additionally, we evaluated the possible underlying neurotoxic mechanisms implicated. The results showed that thememory ability declined in 45-day-old offspring, together with a decrease of catalase and glutamate transaminases activity inspecific brain areas. The present study reveals that exposure to F in early stages of rat development leads to impairment ofmemory in young offspring, highlighting the alterations of oxidative stress markers as well as the activity of enzymes involved in theglutamatergic system as a possible mechanisms of neurotoxicity.